Eco-efficiency analysis by BASF the method. - Saling, Peter
Intention, Goal, Scope, Background. BASF has developed the tool of eco-efficiency analysis to address not only strategic issues, but also issues posed by the marketplace, politics and research. It was a goal to develop a tool for decision making processes which is useful for a lot of applications in chemistry and other industries. Objectives. The objectives were the development of a common tool, which is usable in a simple way by LCA experts and understandable by a lot of people without any experience in this field. The results should be shown in such a way that complex studies are understandable in one view. Method. The method belongs to the rules of ISO 14040 ff. Beyond these life cycle aspect costs, calculations are added and summarized together with the ecological results to establish an eco-efficiency portfolio. Results and Discussion The results of the studies are shown in a simple way, the eco-efficiency portfolio. Therefore, ecological data are summarized in a special way as described in this paper. It could be shown that the weighting factors, which are used in our method, have a negligible impact on the results. In most cases, the input data have an important impact on the results of the study. Conclusions It could be shown that the newly developed eco-efficiency analysis is a new tool, which is usable for a lot of problems in decision making processes. It is a tool which compares different alternatives of a defined customer benefit over the whole life cycle. Recommendations and Outlook. This new method can be a helpful tool in different fields of the evaluation of product or process alternatives. It can be used in research and development as well as in the optimization of customer processes and products. It is an analytical tool for getting more sustainable processes and products in the future.
Keywords: Decision making tool; Eco-efficiency.; Eco-efficiency portfolio; Ecology fingerprint; Life cycle assessment (LCA).; Life cycle management (LCM).; Sustainable development; Metrics and measurement